Pengaruh Penyebaran Informasi Akun Instagram @txtdarisukabumi terhadap Tingkat Pemahaman Informasi Para Pengikutnya - Muhammad Zahran Musyaffa Sanusi; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to determine whether the dissemination of information by the Instagram account @txtdarisukabumi had an effect on the level of understanding of information among its followers. The background of this study stems from the habit of people increasingly relying on social media as a source of information, including for following local issues in their area. This study used a quantitative approach by distributing questionnaires to 100 respondents who were followers of the account. The collected data was then analyzed using descriptive analysis and simple linear regression to see the relationship between information dissemination as variable X and the level of information comprehension as variable Y. The results showed that respondents rated the information dissemination of the @txtdarisukabumi account as high, especially in terms of meeting information needs and motivation to use Instagram to obtain information. Other findings also show that followers' level of understanding of information is high, both in terms of attention to issues and understanding of the context of the information. Regression results show a positive influence between the dissemination of information and the level of understanding of information, which means that the better the information is conveyed, the better the followers' understanding of the message content. Based on these findings, this study concludes that the @txtdarisukabumi account plays a significant role in helping followers understand the local issues presented, so that the dissemination of information through social media can be an effective means of increasing public understanding of the information they consume.